Pelaksanaan Pelayanan Kesehatan Penyandang Disabilitas: Perspektif Fiqih Siyasah - Mustika, Rindy; Yoki Pradikta, Hervin (Universitas Islam Negeri Raden Intan Lampung, 2021)
Article 12 Sub C of Law Number 8 of 2016 concerning Health Services for Persons with Disabilities is present by giving responsibility to the government for the right to health services for persons with disabilities. As explained in Article 12 of Law Number 8 of 2016 namely: